2006
DOI: 10.1111/j.1523-5378.2006.00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility of Helicobacter pylori Strains in a Random Adult Swedish Population

Abstract: The resistance to the antibiotics was lower than expected from patient sample studies, especially for clarithromycin, most probably due to a restrictive prescription policy in the area. Introduction of a test-and-treat strategy in Sweden would only marginally affect the usage of clarithromycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 30 publications
6
27
0
3
Order By: Relevance
“…Treatment with macrolides induces point mutations in the 23S rRNA gene that could result in the acquisition of resistance (41). Despite the heterogeneity of our population (33), mutations involved in CLR r were comparable to mutations reported previously by other studies in Europe, which were mainly A2142G/43G mutations and various combinations of the wild type as well as point mutations related to the presence of multiple isolates (mixed population) in the same biopsy specimen (1,12,31,37,43,44,49). In contrast with data from many previous studies (1,2,11,24), our study identified the A2142C mutation in some strains from children, probably due to the large number of isolates in our study.…”
Section: Vol 49 2011 Two-decade Survey Of H Pylori Resistance In Bmentioning
confidence: 50%
See 1 more Smart Citation
“…Treatment with macrolides induces point mutations in the 23S rRNA gene that could result in the acquisition of resistance (41). Despite the heterogeneity of our population (33), mutations involved in CLR r were comparable to mutations reported previously by other studies in Europe, which were mainly A2142G/43G mutations and various combinations of the wild type as well as point mutations related to the presence of multiple isolates (mixed population) in the same biopsy specimen (1,12,31,37,43,44,49). In contrast with data from many previous studies (1,2,11,24), our study identified the A2142C mutation in some strains from children, probably due to the large number of isolates in our study.…”
Section: Vol 49 2011 Two-decade Survey Of H Pylori Resistance In Bmentioning
confidence: 50%
“…As found for many other countries, H. pylori resistance to TET and AMX was very infrequent in our population (6,14,31,44,50). Therefore, our analysis focused on resistance to CLR, MET, and CIP.…”
Section: Discussionmentioning
confidence: 99%
“…(23). Strains HPAG-KX1A1, HPAG-KX1C1, HPCa-KX2A2, and HPCa-KX2C1 were from the Kalixanda study (31,32). HPAG-KX1 strains were from an de-identified patient with ChAG (HPAG-KX1A1 from the antrum and HPAG-KX1C1 from the corpus).…”
Section: Resultsmentioning
confidence: 99%
“…Globally, the antibiotic resistance of H. pylori ranges from 10 to 80% for metronidazole, 1-25% for clarithromycin, and <1% for amoxicillin [7]. In Sweden, antibiotic resistance for H. pylori is lower than average, with an estimated 16% for metronidazole, 2% for clarithromycin and 0% for amoxicillin [8]. These numbers are based on studies performed more than a decade ago in Sweden and no recent data on antibiotic resistance in H. pylori is available.…”
Section: Introductionmentioning
confidence: 99%